Direct immobilization of biotin on the micro-patterned PEN foil treated by excimer laser - Štofik, Marcel; Semerádtová, Alena; Malý, Jan; Kolská, Zdeňka; Neděla, Oldřich; Wrobel, Dominika; Slepička, Petr (Colloids and surfaces. B, Biointerfaces, 2015)
Polymers with functionalized surfaces have attracted a lot of attention in the last few years. Due to the progress in the techniques of polymer micro-patterning, miniaturized bioanalytical assays and biocompatible devices can be developed. In the presented work, we performed surface modification of polyethylene naphthalate (PEN) foil by an excimer laser beam through a photolithographic contact mask. The aim was to fabricate micro-patterned areas with surface functional groups available for localized covalent immobilization of biotin. It was found out that depending on the properties of the laser scans, a polymer surface exhibits different degrees of modification and as a consequence, different degrees of surface biotinylation can be achieved. Several affinity tests with optical detection of fluorescently labeled streptavidin were successfully performed on biotinylated micro-patterns of a PEN foil. The polymer surface properties were also evaluated by electrokinetic analysis, Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS) and atomic force microscopy (AFM). The results have shown that PEN foils can be considered suitable substrates for construction of micro-patterned bioanalytical affinity assays.
Keywords: naftaleny; polyethyleny; Streptavidin; Lab-on-a-Foil; povrchové vlastnosti; lasery excimerové; Immobilization; biotinylace; Fluorescent affinity assay; Photochemical Processes; streptavidin; Biotin; Surface Properties; fotochemické procesy; mikrotechnologie; laboratoř na čipu; Micropatterning; Lasers, Excimer; PEN foil; Naphthalenes; biotin; Polyethylenes; Microtechnology; Lab-On-A-Chip Devices; Excimer laser; Biotinylation